2015
DOI: 10.4103/0972-6748.160931
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder, emotional intelligence, and locus of control of patients with alcohol dependence

Abstract: Aim:To assess personality disorder (PD), emotional intelligence (EI), and locus of control of alcohol dependent (AD) patients and its comparison with normal controls.Materials and Methods:Based on purposive sampling technique, 33 AD patients were selected from the De-Addiction Ward of Ranchi Institute of Neuro-Psychiatry and Allied Sciences (RINPAS) and 33 matched normal subjects were selected from Ranchi and nearby places. Both the groups were matched on various sociodemographic parameters, that is, age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…Studies have explored personality profiles of patients with AUD in comparison with the general population, opioid dependence syndrome, and HIV. [ 151 152 153 154 ] Diagnostic interview studies have reported lower prevalence (3–6%)[ 105 144 ] than studies using specific personality tools (40% to 56%). Among the personality disorders in AUD male patients, the most commonly reported include antisocial (15–26%), paranoid (9%), and avoidant personality disorders (7–13%), with borderline and dependent personality reported as the lowest.…”
Section: Alcohol-associated Harmsmentioning
confidence: 99%
“…Studies have explored personality profiles of patients with AUD in comparison with the general population, opioid dependence syndrome, and HIV. [ 151 152 153 154 ] Diagnostic interview studies have reported lower prevalence (3–6%)[ 105 144 ] than studies using specific personality tools (40% to 56%). Among the personality disorders in AUD male patients, the most commonly reported include antisocial (15–26%), paranoid (9%), and avoidant personality disorders (7–13%), with borderline and dependent personality reported as the lowest.…”
Section: Alcohol-associated Harmsmentioning
confidence: 99%
“…[ 4 ] Another Indian study that used Millon Clinical Multiaxial Inventory-III found that depressive, narcissistic, and paranoid PDs were prominent in the alcohol dependence group. [ 5 ] Determination of the prevalence of PDs in alcohol-dependent individuals using a clinician-administered semi-structured diagnostic interview will be a valuable addition to the literature from India. In the above context, the present study was conducted to estimate the prevalence of personality disorders in individuals with alcohol dependence syndrome undergoing inpatient treatment and to determine the sociodemographic and clinical correlates of personality disorders in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, vários estudos já investigaram a influência de variáveis psicológicas em comportamentos de saúde geral (Theofilou, 2012;Bragazzi, 2013;Berglund et al, 2014;Cobb-Clark et al, 2014;Ashford e Rayens., 2015;Grisolía et al, 2015;Prakash et al, 2015;Gross et al, 2016;Helvik et al, 2016;Williams et al, 2016; Wong e Anitescu, 2016) e bucal (Chase et al, 2004;Brandão et al, 2006;Lencová et al, 2008;Tiwari et al, 2014;Bryant et al, 2015;;Nunes e Benzaquen, 2016) porém, são raros os estudos que analisaram a influência de variáveis psicológicas na decisão materna sobre como amamentar seu filho de Jager et al, 2013;de Jager et al, 2014;Almeida, 2015).…”
Section: Introductionunclassified